An Overview of Optimization, Characterization, Recovery and Application of Polyhydroxyalkanoates Synthesized by Microorganisms - Mascarenhas, Joyline; Aruna, K. (An Overview of Optimization, Characterization, Recovery and Application of Polyhydroxyalkanoates Synthesized by Microorganisms, 2021)
As we step towards a sustainable future, the biggest hindrance is challenging the efficiency and economic application of plastics in most industries. In this effect, the bacterial polyhydroxyalkanoates (PHAs) appear to be a suitable candidate to replace non-degradable plastics, and confront the environmental pollution caused by its accumulation over the decades. PHA are energy reserves produced by microbial cells that can be utilized during nutrient deficient conditions, and show properties similar to non-degradable plastics used extensively by common people for decades. In addition, they are biodegradable and biocompatible. Hence, in order to replace the existing plastics, PHA accumulating micro-organisms are gaining considerable interest of researchers and environmentalists. The properties of PHAs depend on several physicochemical parameters, and factors like microbial strain, and its growth and nutritional conditions. Hence studying different optimization parameters for PHA accumulation in bacterial cells and its characterization is extremely important, even if produced by same species isolated from different environment. Using biotechnology and interdisciplinary approaches, the PHAs have extensive scope not only in the field of marketing but also in areas of medicine, due to its degradable nature. This monograph gives an overview of the techniques reported in literature to screen PHA accumulators, optimize its accumulation and characterize these polymers using analytical instruments. Besides, various applications of PHAs in diverse fields are also discussed.